Design and Study Cactus Automatic Solar Watering System - Padkaw, Wandee; khutain, Songphon; Warorot, Warapon; Lawong, Amin (Journal of Engineering and Industrial Technology, Kalasin University, 2023)
The study and design of a cactus automatic solar watering system is the focus of this project. The goal is to help cactus growers and measure soil moisture. Furthermore, the water can be turned on and off using the BLYNK Server smartphone app, eliminating the need to visit the garden on a regular basis wherever there is an internet connection. It also uses electricity from solar energy through solar cells to be used in this project. The system experiment from the design of the data security satisfaction inquiry in the system had an average of 4.22 very good. The average quality of the system survey was 4.83, which was the highest. Functionality has a net positive effect of 4.60. The test results showed that the operation of the solar cactus watering system is accurately displayed and that the system can be turned on and off.